2019
DOI: 10.1108/ijhma-08-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Real estate list price anchoring and cognitive ability

Abstract: Purpose This paper aims to revisit the issue of anchoring effects in real estate markets to consider the current dual-processing theory of mind. Design/methodology/approach The effects of high and low anchors in a price estimation task are, thus, explained by both Systems 1 and 2 as these play a key role in the guess of the “correct” list price. The authors also take into account the mediation of overconfidence in the estimates and how confidence relates to cognitive ability. Moreover, the authors nuance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Northcraft and Neale's (1987) findings suggest that anchoring biases influenced both professionals and laypersons but that the laypersons appeared to be more reliant on the pre-set "anchor". Da Silva et al (2019) also demonstrated that the anchoring effect influences both property professionals and non-professionals, and non-professionals are more prone to be influenced. Scott and Lizieri (2012) found a strong anchoring effect on the price perceptions of homebuyers.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Northcraft and Neale's (1987) findings suggest that anchoring biases influenced both professionals and laypersons but that the laypersons appeared to be more reliant on the pre-set "anchor". Da Silva et al (2019) also demonstrated that the anchoring effect influences both property professionals and non-professionals, and non-professionals are more prone to be influenced. Scott and Lizieri (2012) found a strong anchoring effect on the price perceptions of homebuyers.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Following that assumption, a broad spectrum of studies has demonstrated that the initial starting value of the property can serve as an anchor during the appraisal or negotiation process in the real estate market, e.g. Da Silva, et al (2019), Brzezicka (2016. However, it has been argued that anchoring bias may be induced by different mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high precise price generates the highest final sale price, the smallest percentage discount off the list price, and the largest fraction of the surplus to the seller, while just below pricing leads to the lowest final price, the largest percentage discount, and the smallest fraction of the surplus to the seller. (Da Silva, et al, 2019) To revisit the issue of anchoring effects in real estate markets. 90 professional real estate agents and 90 amateur students 30% of the participants were asked to estimate the list price based only on the description of the apartment and the pictures; 30% were told the owner's list price was R$410,000 (the high anchor); 30% were told the owner had a list price of R$310,000 (the low anchor).…”
Section: Student Volunteersmentioning
confidence: 99%
“…Por outro lado, em situações nas quais uma decisão deva ser tomada por um grupo, é possível verificar a redução do viés de ancoragem, ainda que não ocorra a sua total eliminação (Meub & Proeger, 2018). Esse benefício obtido através de uma decisão de grupo ocorre em situações cuja decisão for predominantemente intelectual e/ou factual; se o problema estiver ligado à definição de um valor aleatório ou uma estimativa percentual, a ancoragem acontece no mesmo nível tanto para indivíduos, quanto para discussões em grupo (Leusch et al, 2018) Por mais que a ancoragem seja percebida em menor intensidade em situações que pessoas experientes sejam testadas em suas áreas de atuação (Da Silva et al, 2019;Shan et al, 2019), o viés de ancoragem tem o poder de afetar o julgamento que pessoas que estão acostumadas a tomar decisões parecidas com certa frequência (Broekema et al, 2020;Da Silva et al, 2019). Outros experimentos indicam que pessoas podem ter a sua decisão ancorada em até uma semana após a exposição a um estímulo (Snowman & Kucharska, 2020).…”
Section: Viés De Ancoragemunclassified